The Relationship between Cuff Pressure and Air Injection Volume of Endotracheal Tube: A Study with Sheep Trachea Ex Vivo - Ruixue Wang; Xinlei Qin; Wenyi Zhou; Yujia Zhao; Jiangwen Yin; Zhenggang Cao; Jingwen Zhai; Sheng Wang (Applied Bionics and Biomechanics)
Background. Endotracheal intubation is a widely used treatment. Excessive pressure of the endotracheal tube cuff leads to a series of complications. Here, we used tracheae of sheep to analyze the relationship between the air injection volume and endotracheal tube cuff pressure so as to guide the doctors and nurses in controlling the pressure of the endotracheal tube cuff during clinical work and minimise the risk of complications. Materials and Methods. Forty sheep tracheae were utilised and were divided into five groups according to their diameters. Different sizes of endotracheal tubes were inserted into each trachea, and the cuff pressure with the increase of air injection volume was recorded. The formulas that reflect the relationship between air injection volume and cuff pressure were obtained. Then, sheep tracheae were randomly selected; different types of tubes were inserted, and the stipulated volume of air was injected. The actual pressure was measured and compared with the pressure predicted from the formulas. Statistical analysis was conducted to verify whether the formulas obtained from the first part of the experiment were in accordance with the expert evaluation table, which consists of opinions of several experts. Results. After obtaining 15 formulas, we collected the differences between the theoretical cuff pressure and the actual cuff pressure that satisfied the expert evaluation. Relying on the formulas, the medical turntable was obtained, which is a tool that consists of two round cards with data on them. The top card has a notch. The two cards are stacked together, and as the top card rotates, the data on the bottom card can be easily seen in a one-to-one relationship. Conclusion. The formulas are capable of showing the relationship between the cuff air injection volume and pressure of endotracheal tube cuff. The medical turntable can estimate the air injection volume to ensure that the pressure stays in an acceptable range.